Asymmetric Volatility of the Thai Stock Market. Evidence from High-Frequency Data - THAKOLSRI, Supachok; SETHAPRAMOTE, Yuthana; JIRANYAKUL, Komain (Journal of Advanced Studies in Finance; Vol 6 No 2 (2015): JASF Volume VI Issue 2(12) Winter 2015, 2017)
This study employs the daily data of the Stock Exchange of Thailand to test for the leverage and volatility feedback effects. The period of investigation is during January 4, 2005 to December 27, 2013, which includes the Subprime crisis period in the US that might affect the volatility of stock market return in emerging stock markets. The results from this study show that the US subprime crisis imposes a minimal positive impact on volatility. In addition, the estimations of the three parametric asymmetric volatility models give the results showing some evidence of the volatility feedback and leverage effects. The findings give implications for portfolio diversification and risk management.